Long-term effects of forced migration - Matti Sarvimäki; Roope Uusitalo; Markus Jäntti (Institute for the Study of Labor (IZA), 2009)
We study the long-term effects of human displacement using individual-level panel data on forced migrants and comparable non-migrants. After World War II, Finland ceded a tenth of its territory to the Soviet Union and resettled the entire population living in these areas in the remaining parts of the country. We find that displacement increased the long-term income of men, but had no effect on that of women. We attribute a large part of the effect to faster transition from traditional (rural) to modern (urban) occupations among the displaced.
urn:nbn:de:101:1-20090304306
Keywords: J60; O15; R23; 330; Migration; displaced persons; regional labor markets; Flüchtlinge; Umsiedlung; Kriegsfolgen; Regionaler Arbeitsmarkt; Finnland